Histological changes in the kidneys of cats that died from infectious peritonitis - Borysevych, B.; Kotliarov, E. (Scientific Progress & Innovations, 2022)
The article aimed to find the changes in the kidneys of cats at various forms of infectious peritonitis by histological research methods, which is important for understanding the pathogenesis of this disease. Histological studies of the kidneys of 26 cats that died from a mixed form of infectious peritonitis and 7 cats that died from a dry form of this disease were carried out. It was found out that the character of microscopic changes in this organ did not depend on the form of the disease, but was different depending on the duration of its course. In cats that had been ill for less than 3 weeks before the onset of death, the mesangial-capillary variant of mesangial glomerulonephritis, granular dystrophy, partial plasmolysis, and destruction of the cells of the epithelium of convoluted tubules were found, as a result of which microcysts were formed in the cortical substance in places. In straight tubules, subepithelial edema, swelling and destruction of the basal membranes of the tubule epithelium, destruction and lysis of epithelial cells were found. In the areas where the absence of mesothelium was established, the outer part of the cortical substance was completely disorganized, and renal corpuscles were not detected. Beneath this disorganized part of the cortical substance was a less altered cortical substance in which compacted and non-compacted areas were found. Foci of compacted cortical substance of the kidneys arose due to a significant reduction in the lumen of the convoluted tubules. Single macrophages were found in the lumen of the convoluted tubules both in the compacted and the non-compacted areas of the cortical substance of the kidneys. Hemorrhages were recorded in the stroma of the cortical substance. In cats that had infectious peritonitis for more than 3 weeks, microscopic changes in the kidneys had another character. In the cortical substance, only a few kidney bodies with necrotized glomeruli were found in some places. Disorganized and destroyed convoluted tubules, remnants of convoluted tubules, the proliferation of fibrous connective tissue, and foci of lymphocyte infiltration were found in many areas. Only in some places, convoluted tubules filled with partially destroyed cells were detected, between which a slight growth of fibrous connective tissue was recorded. In the medulla, microscopic changes in the tubules and stroma of the organ were similar to those in the cortex.